(untitled) (Anclajes, 2017)
The articles contained in the volume “Public Interventions, Intimate Configurations: Latin American and Caribbean Women Writers between 1870 and 1940” follow a tradition of feminist criticism focused on the recovery and visualization of the literary production of Latin American and Caribbean women writers.